2017
DOI: 10.21763/tjfmpc.336147
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Measurements with The Newest Vital Sign Instrument Among Adolescents from Dubai, United Arab Emirates

Abstract: Introduction: Assuring high quality health literacy for adolescents is important in the United Arab Emirates to facilitate government's Vision 2021 objectives of superior health and intellectual attainment of young people, as well as to reduce very high prevalence of adolescent obesity and other behavioural and dietary risk factors for health. Methods: In mid-2016, the authors applied the validated Newest Vital Sign Health Literacy instrument to 440 Emirati nationals and Non-Emirati (expatriate) high school st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
(20 reference statements)
0
10
1
Order By: Relevance
“…In 2004, the national health promoting school network was implemented in UAE, including the promotion of healthy behaviour (diet, physical activity, safety, mental, emotional and social health, comprehensive screening [ 21 ]. In a recent study among adolescents in Dubai, UAE, more than one in four had limited health literacy, calling for health literacy training among UAE adolescents [ 22 ]. A strengthening of the health promotion school activities is indicated in order to improve on some of health indicators.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, the national health promoting school network was implemented in UAE, including the promotion of healthy behaviour (diet, physical activity, safety, mental, emotional and social health, comprehensive screening [ 21 ]. In a recent study among adolescents in Dubai, UAE, more than one in four had limited health literacy, calling for health literacy training among UAE adolescents [ 22 ]. A strengthening of the health promotion school activities is indicated in order to improve on some of health indicators.…”
Section: Discussionmentioning
confidence: 99%
“…The Newest Vital Sign has also been revealed to be a reliable and valid instrument in Spanish, Portuguese, and Dutch [ 24 26 ]. The ‘Newest Vital Sign’ was translated and adapted to the Arabic language and tested for cultural suitability [ 27 , 28 ]. It is one of the most frequently adapted tools to assess health literacy in the Eastern Mediterranean Region [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The majority of Generation Z had marginal or inadequate HL levels. Awofeso et al 24 found that HL levels were moderate in their study of adolescents, while Berens et al 6 found that HL levels of almost half of adolescents were inadequate and problematic. It is known that children with lower HL levels are often associated with poorer health behaviors.…”
Section: Generation Zmentioning
confidence: 96%
“…However in some research, the correlation between health behaviors of adolescents and their HL scores has been positive. [23][24][25] Thus, it is of importance that HL levels of Generation Z members who are in the adolescent period should be improved. McDaid 26 writes that effective HL interventions can positively influence education and academic performance, which can have long-term benefits across the life course.…”
mentioning
confidence: 99%